Work With Public Health Partners to Protect Water Quality. Issue 10 (1st October 2017) - Allgeier, Steven C.; Blake, Robert G.; Yoder, Jonathan S.
Abstract : Public health agencies' expertise and the data they gather can play a valuable role in providng a safe drinking water supply. Alliances with these agencies facilitate exchanges of information to spot water quality changes early and ensure timely, appropriate event response.